Effect of concrete cover thickness and main reinforcement ratio on flexural behavior of RC beams strengthened by NSM-GFRP bars - Hesham EL-Emam; Alaa El-Sisi; Ramy Reda; Mohamed Seleem; Mohamed Bneni (Fracture and Structural Integrity)
Experimental and numerical programs were conducted to investigate the effect of concrete cover and area of main steel reinforcement on the flexural behavior of strengthened RC beams by near-surface mounted glass fiber reinforced polymeric (NSM GFRP) bars of different lengths. Nine beams divided into three main groups were tested under four-point bending. The three beams of the first group were strengthened by different lengths of GFRP bars and having a concrete cover of 50 mm, while the three beams in the second group were strengthened in a similar manner as those of the first group but the concrete cover was 30 mm. The main steel reinforcement in the first and second groups was 210. The three beams of the third group were similar to those of the first and second group but the main steel reinforcement was 216. The 3-D FE commercial ANSYS program was used for the numerical work. The experimental results showed that decreasing the concrete cover increased the flexural capacity of the strengthened RC beams but this improvement disappeared by decreasing the NSM GFRP bar length. The numerical results showed an agreement with the experimental results.